On the description of exotic hadron states within QCD sum rules - Lucha Wolfgang (EPJ Web of Conferences, 2017)
Revisiting the QCD sum-rule description of exotic hadron states, we argue that, in order to arrive at trustable analyses of, for instance, strong decay widths of multiquarks, it is inevitable to adopt the QCD sum-rule approach beyond the leading perturbative level.